2021
DOI: 10.1101/2021.05.15.443978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fc-independent neutralization of SARS-CoV-2 by recombinant human monoclonal antibodies

Abstract: The use of passively-administered neutralizing antibodies is a promising approach for the prevention and treatment of SARS-CoV-2 infection. Antibody-mediated protection may involve immune system recruitment through Fc-dependent activation of effector cells and the complement system. However, the role of Fc-mediated functions in the efficacious in vivo neutralization of SARS-CoV-2 is not yet clear. Delineating the role this process plays in antibody-mediated protection will have a great impact on the design of … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Moreover, Fcmediated complement activation can exert a broad range of immunomodulatory functions, with activation of C1q resulting in antibody-mediated complement activation, and complement-dependent cytotoxicity. However, a recent study showed the diminished role of the Fc region in protecting against lethal SARS-CoV-2 infections in K18-hACE2 transgenic mice [42]. This study showed that potent NAbs do not rely on Fc effector functions to provide optimal protection when administered as therapy.…”
Section: What Is the Role Of Antibody Fc Portion In Therapeutic Antibodies Against Sars-cov-2?mentioning
confidence: 85%
“…Moreover, Fcmediated complement activation can exert a broad range of immunomodulatory functions, with activation of C1q resulting in antibody-mediated complement activation, and complement-dependent cytotoxicity. However, a recent study showed the diminished role of the Fc region in protecting against lethal SARS-CoV-2 infections in K18-hACE2 transgenic mice [42]. This study showed that potent NAbs do not rely on Fc effector functions to provide optimal protection when administered as therapy.…”
Section: What Is the Role Of Antibody Fc Portion In Therapeutic Antibodies Against Sars-cov-2?mentioning
confidence: 85%